Penggunaan layanan informasi untuk meningkatkan pemahaman tentang pendidikan seksual sejak dini pada murid Sekolah Dasar (SD) - Devi Ratnasari; Neng Triyaningsih Suryaman; Djoni Aminuddin (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
Children become victims of sexual violence cause adverse effects including traumatic sexualization, stigmatization, betrayal, and powerlessness. This research is conduced as an effort to prevent victims of sexual violence in children through the early introduction of sexual education, and aims to encourage students to have an understanding of education sexual good since early. Students are expected to know and avoid if there is an indication of sexual violence that will occur. This research is conducted using information services to improve the understanding of sexual education early on elementary school students. This research aims to test the effectiveness of information services in improving the understanding of sexual education early on elementary school students. This research uses a research method of pre experimental design with one group approach pre-test and post-test one group design. Research hypothesis tested using non-parametric analysis due to the correlation of research samples and the data in ordinal form. Hypotheses test result show a significance score of 0,02 smaller than α, and are in the rejection area α = 0,05. This suggests the hypothesis is accepted that the use of information services effectively enhances the understanding of sexual education early on elementary school students